An Economy Efficiency Analysis of Non Pearl River Delta Region and nearby cities in Guangdong of China - Jia-Zheng Lin; Dr. Hyung-Ho Kim, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Non Pearl River delta region is the weak zone of economy development in Guangdong province and it's lack of discussion about economic efficiency all the time. The purpose of this study is aim to evaluate the economy efficiency of Non Pearl River Delta Region cities relatively, so the nearby cities such as Foshan, Huizhou, Zhongshan, Jiangmen and Zhaoqing were brought in, by analyzed the data from Guangdong year book in 2014-2018 with DEA-Malmquist and SSBM analysis method, the results show that the efficiency of economic development difference between each city is bigger, north region and east region is generally low and some problems had be found. In this study three aspects were presented according the analysis result, such as the allocation of resources, scientific and technological innovation, coordinated development between regions. Those recommendations would be useful for the region's manager to make an efficient decision of economy development and balance the development level of the cities in Guangdong province China.